2022
DOI: 10.5114/ada.2022.113805
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the association of atopy and aeroallergen sensitization and chronic spontaneous urticaria

Abstract: Introduction: Chronic spontaneous urticaria (CSU) is a common skin allergic reaction with an unknown mechanism. There is inadequate evidence to support the role of aeroallergen sensitization in CSU. Aim: The present study was conducted to investigate the association between the aeroallergen sensitivity and CSU. Material and methods: In this cross-sectional study, 91 patients with CSU were recruited. Information on demographic characteristics was collected. The skin prick test (SPT) for most prevalent aeroaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The positive sensitization rate of patients with CU to various allergens according to the skin prick test (SPT) or serum-specific IgE test ranged from 17.2–95.83% ( Table 1 ), which was significantly higher than that of healthy individuals ( 13 – 33 ). Among the allergens identified in patients with CU, house dust mites (HDM) are often the most common ( 13 , 14 , 16 , 26 , 29 ), followed by weed (mugwort and ragweed) and tree pollen, cereal pollen, cockroaches, weeds, cat hair, rat, and Candida albicans and mixed molds ( 17 , 19 , 21 , 22 , 31 , 32 ). In addition, an association between CU and Anisakis simplex (As) sensitization has been reported, and the sensitization rates to pollen, dander, and mold in patients with CU with sensitization to As (CU/As+) were significantly higher than those in patients without As sensitization (CU/As-) ( 18 ).…”
Section: High Prevalence Of Atopy In Cumentioning
confidence: 99%
“…The positive sensitization rate of patients with CU to various allergens according to the skin prick test (SPT) or serum-specific IgE test ranged from 17.2–95.83% ( Table 1 ), which was significantly higher than that of healthy individuals ( 13 – 33 ). Among the allergens identified in patients with CU, house dust mites (HDM) are often the most common ( 13 , 14 , 16 , 26 , 29 ), followed by weed (mugwort and ragweed) and tree pollen, cereal pollen, cockroaches, weeds, cat hair, rat, and Candida albicans and mixed molds ( 17 , 19 , 21 , 22 , 31 , 32 ). In addition, an association between CU and Anisakis simplex (As) sensitization has been reported, and the sensitization rates to pollen, dander, and mold in patients with CU with sensitization to As (CU/As+) were significantly higher than those in patients without As sensitization (CU/As-) ( 18 ).…”
Section: High Prevalence Of Atopy In Cumentioning
confidence: 99%
“…Studies have found that the prevalence of IgE sensitization to various allergens, tested by skin prick test (SPT) or serum-specific IgE, in CU patients ranges from 17.2% to 95.83% (as shown in Table 1), all significantly higher than the healthy population . Among the allergens found in CU, house dust mites (HDM) are often the most common 10,11,13,22,25 , followed by grass (mugwort and ragweed) and trees pollen, cereal pollen, cockroach, weeds, cat hair, rat, Candida albicans and mixed molds have also been reported significantly increased in CU 14,16,18,19,26,28 , and an association of CU with sensitization to Anisakis simplex has also been described 15 . Studies have also found that multiple allergens IgE sensitization is more common than single allergen IgE sensitization, and sensitization to one allergen may predispose to sensitization to other allergens in CU 15,31 .…”
Section: High Prevalence Of Atopy In Cumentioning
confidence: 99%
“…Recently, sensitization to aeroallergens has been considered a possible factor contributing to development of CSU. Esmaeilzadeh et al [1] mention that in CSU, the frequency of urticaria episodes fluctuates throughout the days and seasons, suggesting a possible contribute of aeroallergen sensitization to the development of CSU. Refaat et al [2] published a study including 200 patients with CSU, also supporting that sensitization to aeroallergens, namely mites, should be considered as a probable cause of CSU development.…”
Section: Introductionmentioning
confidence: 99%